2020
DOI: 10.1111/vco.12571
|View full text |Cite
|
Sign up to set email alerts
|

Toceranib phosphate in the treatment of canine thyroid carcinoma: 42 cases (2009‐2018)

Abstract: Thyroid carcinoma is the most common endocrine malignancy in dogs. Thyroidectomy and radiation therapy control local disease, yet are not always feasible, and efficacious medical therapies need to be identified. Toceranib phosphate has been reported to provide clinical benefit (CB) in dogs with thyroid carcinoma, while its role in treatment-naïve thyroid tumours has not been well-described. The objective of this study was to describe the use of toceranib in the management of thyroid carcinomas in dogs in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 61 publications
(152 reference statements)
4
45
1
1
Order By: Relevance
“…Although a necropsy was not performed, it is possible that this patient experienced a treatment-associated grade 5 gastrointestinal AE. This case highlights the fact that, while most dogs have only mild to moderate AEs associated with toceranib, it is not without risk [16][17][18][19][20][21][22][23][24][25][26][27]33]. Given that earlier studies evaluating toceranib doses of 2.5 to 3.5 mg/kg found no differences in biologic activity observed at higher doses, it may be reasonable to administer toceranib at a dose between 2.4 and 3.0 mg/kg to avoid severe gastrointestinal toxicity and frequent drug holidays when treating dogs with insulinoma [32,34].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although a necropsy was not performed, it is possible that this patient experienced a treatment-associated grade 5 gastrointestinal AE. This case highlights the fact that, while most dogs have only mild to moderate AEs associated with toceranib, it is not without risk [16][17][18][19][20][21][22][23][24][25][26][27]33]. Given that earlier studies evaluating toceranib doses of 2.5 to 3.5 mg/kg found no differences in biologic activity observed at higher doses, it may be reasonable to administer toceranib at a dose between 2.4 and 3.0 mg/kg to avoid severe gastrointestinal toxicity and frequent drug holidays when treating dogs with insulinoma [32,34].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, in the initial phase I study for toceranib, as well as subsequent off-label investigations of toceranib, clinical responses were observed in dogs with a spectrum of solid tumour types [18][19][20][21][22][23][24][25][26][27]. More recently, a case report described a dog diagnosed with metastatic insulinoma experiencing long-term glycemic control with toceranib [28].…”
Section: Introductionmentioning
confidence: 99%
“…Toceranib phosphate (Palladia®; Zoetis Animal Heath, Madison, NJ, USA) is a small molecule inhibitor with similar molecular targets to sunitinib, some of which have been identi ed in two canine tumours of neuroendocrine histology [23][24][25]. Moreover, in the initial phase I study for toceranib, as well as subsequent off-label investigations of toceranib, clinical responses were observed in dogs with a spectrum of solid tumour types [26][27][28][29][30][31][32][33][34][35][36]. More recently, a case report described a dog diagnosed with metastatic insulinoma experiencing long-term glycemic control with toceranib [37].…”
Section: Introductionmentioning
confidence: 99%
“…There have been few studies of the relation-ship between tumor type and prognosis, but our study shows that epithelial tumors have a low recurrence rate and a high survival rate. In the previous studies assessing toceranib, clinical benefits have mainly been shown in epithelial tumors ('-carcinoma') and MCTs [1,6,10,11,13,14,18]. Conversely, few studies have reported effects on mesenchymal tumors such as GIST, OSA, injection site sarcoma, and histiocytic sarcoma, and these studies were limited by small populations [11,18,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Various reports have described the evaluation of toceranib [7,8]. Apart from MCTs [6,9], off-label uses have been described in a variety of tumors, including those of epithelial origin (apocrine gland anal sac adenocarcinoma [AGASA] [10,11], squamous cell carcinoma [SCC] [12], hepatocellular carcinoma [13], nasal carcinoma [11], thyroid carcinoma [14], and mammary gland tumor [15]), mesenchymal origin (osteosarcoma [OSA] [11,16,17], gastrointestinal stromal tumor [GIST] [18], and melanoma [5]), and round cell origin (lymphoma [19]). In one study that reported toceranib's use in the treatment of solid tumors (AGASA, OSAs, thyroid carcinoma, and head and neck carcinoma), a clinical benefit was observed in 63/85 (74.1%) dogs [11].…”
Section: Introductionmentioning
confidence: 99%